EFEKTIVITAS MORINGA OLEIFERA SEBAGAI ANTIHIPERTENSI: LITERATURE REVIEW - Gratsia Victoria Fernandez; Imelda Sirait; Vivi Meiti Berhimpong (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Hypertension is a chronic medical condition in which the blood pressure in the arteries increases and can lead to heart disease and deadly strokes. One of the non-pharmacological therapies currently being developed to reduce high blood pressure is to consume herbal plants. The herbal plant used is the Moringa tree (Moringa Oleifera). The purpose of this literature review is to explain the effectiveness of the consumption of Moringa plants as an antihypertensive. The researched method used a literature studied approached with journals as sources. Searched of researched articles across multiple databases used keywords over a five year period. The results of the studied, consumption of Moringa Oleifera could affect the reduction of high blood pressure. This was due to various phytochemical compounds, bioactive compounds, polar compounds, vitamin C, potassium (K), magnesium (Mg), and calcium (Ca). Thus, Moringa Oleifera could provided the desired effect as a natural high blood pressure controlled drug and could been said as an alternative medicine. Moringa Oleifera could been combined with other herbal plants and medical drugs in controlling high blood pressure.